THALASSEMIA AND VENOUS THROMBOEMBOLISM - Julien Succar; Khaled M. Musallam; Ali T Taher (Mediterranean Journal of Hematology and Infectious Diseases, 2011)
Although the life expectancy of thalassemia patients has markedly improved over the last few decades, patients still suffer from many complications of this congenital disease. The presence of a high incidence of thromboembolic events, mainly in thalassemia intermedia, has led to the identification of a hypercoagulable state in these patients. In this review, the molecular and cellular mechanisms leading to hypercoagulability in thalassemia are highlighted, with a special focus on thalassemia intermedia being the group with the highest incidence of thrombotic events as compared to other types of thalassemia. Clinical experience and available clues on optimal management are also discussed